Two new species of Squalius, S. adanaensis and S. seyhanensis (Teleostei: Cyprinidae), from the Seyhan River in Turkey - Turan, Davut; Kottelat, Maurice; Doğan, Esra (Zootaxa, 2013)
Two new species of Squalius are described from the Seyhan River drainage in Turkey: S. adanaensis from the lower part of the drainage and S. seyhanensis from the upper part. Squalius adanaensis is distinguished from the other species of the genus in Anatolia, among other characters, by having the flank scales with a dark spot on each scale pocket but covered by the posterior margin of the previous scale, and very few melanophores along the posterior margin; 38–42 + 1–2 lateral line scales; and a maximum known size of 157 mm SL. Squalius seyhanensis is distinguished from other species of the genus in Anatolia, among other characters, by having the flank scales with a dark spot on each scale pocket, exposed, and densely-set melanophores along the posterior margin, forming a conspicuous reticulate pattern; 42–44 + 1–2 lateral line scales; and a maximum know size of 240 mm SL.